(untitled) (AYUSHDHARA, 2024)
Anacyclus pyrethrum, commonly known as “Aqarqarha” in Unani medicine has been a prominent herb in traditional medicine systems for centuries due to its diverse therapeutic properties. In recent years, there has been growing interest in exploring its medicinal uses and pharmacological effects. This review aims to provide a comprehensive overview of Aqarqarha, encompassing its traditional uses, phytochemical composition, pharmacological activities, and potential therapeutic applications. Aqarqarha exhibits a wide array of pharmacological activities, including neuroprotective, anti-inflammatory, analgesic, aphrodisiac, antioxidant, and immunomodulatory effects, making it a promising candidate for the management of various health conditions. Moreover, its phytochemical profile comprises various bioactive compounds such as alkamides, sesquiterpene lactones, flavonoids, and polyacetylenes, which contribute to its medicinal properties. This review aims to consolidate the existing knowledge on Aqarqarha, providing a basis for further research and development in both traditional and modern medicine. Furthermore, it highlights gaps in current knowledge and identifies areas for future research, such as clinical trials, mechanistic studies, formulation development, and regulatory considerations. By synthesizing existing information and proposing future directions, this review seeks to facilitate a deeper understanding of Aqarqarha’s therapeutic potential and promote its integration into evidence-based healthcare practices.